Hubungan Perilaku Picky eater dengan Tingkat Kecukupan Zat Gizi dan Status Gizi Anak Usia Prasekolah Di Gayungsari - Adhelia Niantiara Putri; Lailatul Muniroh (Amerta Nutrition, 2019)
Background: Picky eater is unwillingness to eat unfamiliar food or try new food as well as strong food preference. Picky eater behaviour in preschool-aged children might cause an insufficient intake of food and lead to impaired growth. Objectives: This study aimed to analyze the correlation between picky eater with adequacy level of intake and nutritional status among preschool children in KB-TK Al-Hikmah Surabaya.Methods: This study was an analytic observational study with a cross-sectional design. 45 subjects aged 41-59 months participated in this study. Simple random sampling method was used to select the sample of this study. Data were collected by measuring height, weight, filling Child Eating Behaviour Questionnaire, and nutrient intake by filling Semi-Quantitative Food Frequency Questionnaire. All data were analyzed using Spearman’s Rho test using SPSS v25.0.Results: This study discovered that 57.6% of subjects had picky eater behaviour, 40% subject had high intake of energy but 95,6% subject had low fibre intake, 22.2% subject were malnutrition, 20% subject were wasting, 13.3% subject were categorized as stunting. Around 23.1% subject with picky eater behaviour had malnutrition. Energy intake level (p=0.000, r=0.717), carbohydrate (p=0.000, r=0.566), protein (p=0.007, r=0.396), dan fat (p=0.000, r=0.599) were correlated to picky eater behaviour. Subjects with picky eater tend to have lower intake level compared to non-picky eater subjects. All subjects have low fibre intake. Nutritional status were not correlated to picky eater behaviour with WAZ (p=0.444), HAZ (p=0.366) and WAZ (p=0.235). Conclusions: There were correlation between picky eater behaviour and intake level. Subject with this behaviour needs to improve their intake level to prevent incident of underweight.ABSTRAKLatar belakang: Picky eater adalah perilaku memilih-milih makanan yang ditandai dengan terbatasnya jumlah pilihan makanan. Kejadian picky eater pada anak prasekolah berakibat kekurangan asupan jangka panjang, sehingga dapat mengganggu pertumbuhan anak.Tujuan: Tujuan penelitian ini adalah menganalisis hubungan antara perilaku picky eater dengan tingkat kecukupan zat gizi dan status gizi pada anak usia prasekolah di KB-TK Al-Hikmah Surabaya.Metode : Penelitian ini merupakan penelitian observasional analitik dengan desain cross-sectional. 45 subyek dengan usia 41-59 bulan berpartisipasi dalam penelitian ini. Metode simple random sampling digunakan untuk pengambilan sampel. Pengumpulan data meliputi pengukuran antropometri, pengisian Child Eating Behavior Quiessionare, dan Semi-Quantitative Food Frequency Questionnare. Seluruh data dianalisis menggunakan SPSS v25.0 dengan uji Spearman’s Rho.Hasil : Hasil menunjukkan 57,8% responden memiliki perilaku picky eater. Tingkat kecukupan zat gizi memiliki hasil beragam dengan tingkat kecukupan serat kurang. Terdapat 22,2% subyek dengan status gizi kurang, 13,3% subyek dengan stunting, dan 20% subyek dengan wasting. Hasil penelitian ini menunjukkan adanya hubungan antara tingkat kecukupan energi (p=0,000, r=0,717),  karbohidrat (p=0,000, r=0,566), protein (p=0,007, r=0,396), dan lemak (p=0.000, r=0,599) dengan kejadian picky eater namun tidak berhubungan dengan tingkat kecukupan serat (p=0,825), status gizi BB/U(p=0,444), TB/U(p=0,366) dan BB/TB(p=0,235).Kesimpulan : Subyek yang berperilaku picky eater memiliki tingkat kecukupan zat gizi lebih rendah. Picky eater berhubungan tingkat kecukupan zat gizi. Responden dan subyek dengan perilaku ini sebaiknya memperbaiki kebiasaan makan dan memperbanyak konsumsi serat untuk mencegah kejadian gizi kurang